2019
DOI: 10.5696/2156-9614-9.24.191204
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons in Sediment and Health Risk of Fish, Crab and Shrimp Around Atlas Cove, Nigeria

Abstract: Background. Polycyclic aromatic hydrocarbons (PAHs) are toxic contaminants and pose health risks to humans and the ecosystem due to their persistence in the environment. Objectives. This study determined the concentrations of PAHs in sediment, two species of fish (Drepane africana and Pomadasys jubelini), crabs (Callinectes amnicola) and shrimps (Penaeus notialis) around the Atlas Cove jetty, Lagos, Nigeria. Methods. Polycyclic aromatic hydrocarbons were extracted from fish, shrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
(55 reference statements)
0
24
3
4
Order By: Relevance
“…The total number of PAHs identified in CLARAIS GARIEPINUS isolated from Ekulu River (from the downstream, upstream and POD) were higher when compared to the control. The concentration of the individual PAHs assayed for in fishes were also higher than the control Olaiyinka et al [16].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The total number of PAHs identified in CLARAIS GARIEPINUS isolated from Ekulu River (from the downstream, upstream and POD) were higher when compared to the control. The concentration of the individual PAHs assayed for in fishes were also higher than the control Olaiyinka et al [16].…”
Section: Resultsmentioning
confidence: 75%
“…Using the Fl/Py methodology, it suggested that they were petrogenic for the upstream and pyrogenic for the PAHs that accumulated in Clarais Gariepinus at the POD. The results obtained by Olayinka et al [16] also suggested that the PAHs detected in fishes were of both petrogenic and pyrogenic. The petrogenic sources of PAHs observed in Clarais gariepinus obtained from the upstream can be as a result of runoffs from oil contaminated effluents from the industry while the pyrogenic sources at the POD can be assigned to the combustion that occurs in the roofing sheet industry nearby.…”
Section: Resultsmentioning
confidence: 90%
“…19 The dietary intake of these food toxicants through food consumption is a topic of public health concern as a result of the continuous daily exposure to concentrations of these toxicants which exceed normal safe limits for human consumption. 19,20,68,82 This view was also shared regarding the increased consumption of a fried-tuna-related food in Abidjan, Cote d'Ivoire. 76 A number of health risk assessments made in different parts of SSA have shown that these exposures have the capacity to bring about carcinogenic and mutagenic risks.…”
Section: Health Risk Assessments Of Pah Contamination In Ssamentioning
confidence: 92%
“…[16][17][18][19] Whenever they are released into the environment, they travel long distances due to their persistent nature, accumulate in, and harm plants, animals, and inadvertently humans. [20][21][22] Typically, the low-molecular-weight PAHs dissolve in water, and the high-molecular-weight PAHs are adsorbed onto living organisms or particles found in water. 23,24 Examples include benz(a)anthracene, naphthalene, pyrene, dibenz[a, h]anthracene, benzo[k]fluoranthene, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic Aromatic Hydrocarbon (PAHs) are harmful and carcinogenic compound present in the environment (Tsang et al, 2011;Christensen and Arora, 1998). It is also environmentally ubiquitous and cause adverse effects on the environment (Olayinka et al, 2019). Furthermore, it also serves as pervasive pollutants which have carcinogenic and mutagenic properties (Wilson and Joins, 1993;Menzie and Potokib, 1992).…”
Section: Introductionmentioning
confidence: 99%